Einführung und Evaluierung des praktischen Jahres an der Tierärztlichen Hochschule Hannover [Introduction and evaluation of final-year practice-oriented education at the University of Veterinary Medicine in Hanover, Germany] - Wagels, Rolf; Tipold, Andrea; Feige, Karsten (GMS Zeitschrift für Medizinische Ausbildung, 2008)
[english] The introduction of a year of practice-oriented education should provide students of the University of Veterinary Medicine in Hanover greater integration in the clinical and scientific setting in order to gain “real-life” experience for their later profession before the end of their studies. This year replaces the old 9th and 10th semesters and builds a bridge between the well-organized and structured studies and the later profession. It includes internships outside the university in private practice, private clinics, slaughterhouses, etc., and a practical semester that can be completely at any time of the year in clinics and other institutes of the university. The online evaluation of this year has been positive. [german] Mit der Einführung des praktischen Jahres sollen die Studierenden der Tierärztlichen Hochschule Hannover (TiHo) stärker in den klinischen und wissenschaftlichen Alltag eingebunden werden, um schon vor Ende des Studiums praxisnahe Erfahrungen zu sammeln. Das praktische Jahr ersetzt das bisherige 9. und 10. Semester und bildet so die Überleitung zwischen dem eng organisierten Studium und der anschließenden beruflichen Laufbahn. Es beinhaltet die Praktika außerhalb der TiHo in Tierarztpraxen, Privatkliniken, Schlachthöfen, etc. und ein internes praktisches Semester, welches das gesamte Jahr über in den Einrichtungen der TiHo abgeleistet werden kann. Die Online-Evaluierung dieses Jahres verlief positiv.